Matched unrelated donor transplantation versus haploidentical transplantation with post-transplant cyclophosphamide in children with acute myeloid leukemia: a PDWP-EBMT study - Ruggeri, Annalisa; Santoro, Nicole; Galimard, Jacques-Emmanuel; Kalwak, Krzysztof; Algeri, Mattia; Zubarovskaya, Ludmila; Czyzewski, Krzysztof; Skorobogatova, Elena; Sedlacek, Petr; Besley, Caroline; Balduzzi, Adriana; Bertrand, Yves; et al. (Haematologica, 2024)
In children with acute myeloid leukemia (AML) who lack a human leukocyte antigen (HLA) identical sibling, the donor can be replaced with an HLA-matched unrelated donor (MUD) or a haploidentical donor (haplo). We compared outcomes of patients <18 years with AML in first and second complete remission (CR1 and CR2) undergoing a hematopoietic stem cell transplantation (HCT) either with a MUD with anti-thymocyte globulin (ATG) (N=420) or a haplo HCT with post-transplant cyclophosphamide (PT-CY) (N=96) after a myeloablative conditioning regimen (MAC) between 2011 and 2021, reported to the European Society for Blood and Marrow Transplantation. A matched pair analysis was performed to adjust for differences among groups. The final analysis was performed on 253 MUD and 95 haplo-HCT. In the matched cohort, median age at HCT was 11.2 and 10 years and median year of HCT was 2017 and 2018, in MUD and haplo-HCT recipients, respectively. The risk of grade III-IV acute graft-versus-host disease (aGVHD) was significantly higher in the haplo group (hazard ratio [HR]=2.33, 95% confidence interval [CI]: 1.18-4.58; P=0.01). No significant differences were found in 2 years overall survival (OS; 78.4% vs. 71.5%; HR=1.39, 95% CI: 0.84-2.31; P=0.19), leukemia-free survival (LFS; 72.7% vs. 69.5%; HR=1.22, 95% CI: 0.76-1.95; P=0.41), CI of relapse (RI; 19.3% vs. 19.5%; HR=1.14, 95% CI: 0.62-2.08; P=0.68) non-relapse-mortality (NRM; 8% vs. 11%; HR=1.39, 95% CI: 0.66-2.93; P=0.39) and graft-versus-host free relapse-free survival (GRFS; 60.7% vs. 54.5%, HR=1.38, 95% CI: 0.95-2.02; P=0.09) after MUD and haplo-HCT respectively. Our study suggests that haplo-HCT with PT-CY is a suitable option to transplant children with AML lacking a matched related donor.
Keywords: Leukemia, Myeloid, Acute; transplantace hematopoetických kmenových buněk; Infant; Humans; Transplantation, Haploidentical; kojenec; dítě; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Child; Female; příprava pacienta k transplantaci; výsledek terapie; lidé; Unrelated Donors; haploidentická transplantace; předškolní dítě; testování histokompatibility; nepříbuzný dárce; ženské pohlaví; Male; nemoc štěpu proti hostiteli; Adolescent; Treatment Outcome; Transplantation Conditioning; Cyclophosphamide; Histocompatibility Testing; mužské pohlaví; Child, Preschool; cyklofosfamid; akutní myeloidní leukemie; mladiství